2020
DOI: 10.1111/jbi.13919
|View full text |Cite
|
Sign up to set email alerts
|

Strong genetic structure in a widespread estuarine crab: A test of potential versus realized dispersal

Abstract: Aim: Genetic structure has proven difficult to predict for marine and estuarine species with multi-day pelagic larval durations, since many disperse far less than expected based on passive transport models. In such cases, the gap between potential and realized dispersal may result from larval behaviours that evolved to facilitate retention and settlement in favourable environments. Behaviour is predicted to play a particularly key role in structuring truly estuarine species, which often moderate their behaviou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 62 publications
0
6
0
Order By: Relevance
“…Sequence data from these specimens were generated previously, as described in Tepolt, Blakeslee, et al (2020). As the largest and most accessible neural organ, the thoracic ganglion was chosen for sequencing due to its probable functional importance to the parasite's impact on host behaviour.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Sequence data from these specimens were generated previously, as described in Tepolt, Blakeslee, et al (2020). As the largest and most accessible neural organ, the thoracic ganglion was chosen for sequencing due to its probable functional importance to the parasite's impact on host behaviour.…”
Section: Methodsmentioning
confidence: 99%
“…Libraries were sequenced across seven lanes of an Illumina HiSeq 2000 in 50‐bp single‐end reads at the University of Utah High Throughput Genomics Core Facility. Further methodological details, including the results of a population genomic investigation of the host crab, can be found in Tepolt, Blakeslee, et al (2020).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Even so, the contrasting patterns of observed genetic diversity in our study reflect variation in just a single mitochondrial marker. Future studies with more nuclear markers could resolve this issue (e.g., population genome sequencing; Reitzel et al 2013;Tepolt et al 2020). Indeed, L. saxatilis has recently become the subject of numerous genomic investigations of ecotypic differentiation across multiple European populations (e.g., Johannesson et al 2017Johannesson et al , 2020Kess et al 2018;Morales et al 2019), approaches that could be applied to North American populations to further resolve its population structure throughout the North Atlantic.…”
Section: Does L Littorea Exhibit Greater Genetic Variability and Higher Effective Population Sizes Compared To L Saxatilis In The North Amentioning
confidence: 99%
“…In fact, some studies have found pelagically dispersing species to exhibit relatively high levels of genetic structure than might otherwise be expected considering their larval duration (Milá et al 2017;Mertens et al 2018). For example, the white-fingered mud crab, Rhithropanopeus harrisii, has a planktotrophic larval stage and demonstrates strong genetic structure in Gulf and Atlantic estuaries in its North American range, with larval retention behaviors likely playing a role (Tepolt et al 2020). Second, genetic variability could be lower than expected for marine taxa with pelagically dispersing larvae if there is high larval mortality during the pelagic stage (i.e., type III survivorship curves) (Hedgecock 1994).…”
Section: Introductionmentioning
confidence: 99%